Bolted end-plate tube connections subject to tension and bending - Fidalgo, Augusto; Packer, Jeffrey A. (Canadian journal of civil engineering, 2024)
A large amount of research has been undertaken on tubular bolted end-plate connections loaded in axial tension, and considerably less on such connections in flexure. This paper studies the combined effects of these two loads and presents the first laboratory tests on these connections under combined tension and flexure. Using validated finite element models, a parametric study with 360 numerical models is performed on these connections under axial and eccentric tension loads. After screening this database of experimental tests and numerical results to isolate only connection failure modes, current design methods for predicting the connection capacity under eccentric tension are evaluated and revised. In addition, based on interaction curves, a novel approach is proposed to design these splices under combined loads. For all methods, the use of the plate ultimate and yield stress was compared for the end-plate material strength parameter. Lastly, a reliability analysis is performed for the application of the recommended design methods to Canadian practice.